Circular Economy and Value Chains (Life Cycle Analysis) - Kovačič Lukman, Rebeka; Brglez, Kristijan (Mastering Sustainability in Supply Chains, 2026)
Adopting the circular economy concept is of paramount significance for sustainable development, societal metamorphosis, and alleviating pressures on natural systems. This paradigm shift transcends linear consumption models, championing a resource-efficient system where conservation, renewal, and judicious resource use prevail. Integral to this transformation are value chains, pivotal in reshaping production methods, prolonging product longevity, and advocating reuse and recycling. A cornerstone tool in translating circular economy principles into action is Life Cycle Analysis (LCA). LCA meticulously evaluates products' holistic environmental, social, and economic ramifications, pinpointing areas for enhancement and empowering informed decisions towards sustainability. A profound grasp of the circular economy coupled with instrumental tools such as LCA facilitates the sustainable stewardship of resources, an imperative for harmonizing human advancement with environmental preservation in times ahead.